Non-methane total hydrocarbon purification catalyst composition, catalyst, preparation method and application
The problem of sulfur intolerance of traditional catalysts is solved by using soluble ferrous sulfate, alkaline earth metal hydroxide and manganese source compounds, and covering the surface with TiO2 or SiO2 shells, achieving longer service life and lower production costs.
Patent Information
- Application Number
- CN202211507730.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-25
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-11-25
AI Technical Summary
Traditional non-methane total hydrocarbon purification catalysts have shorter lifespans and higher costs due to sulfur intolerance.
A non-methane total hydrocarbon purification catalyst composition, including soluble ferrous sulfate, alkaline earth metal hydroxide and manganese source compound, is prepared by solid-solid mixing and calcining, and the TiO2 or SiO2 shell is further covered on the catalyst surface.
It improves the water and sulfur resistance of the catalyst, extends its life and reduces production costs.
Smart Images

Figure CN116237064B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the fields of chemical industry, energy, environmental protection, and in particular to a non-methane total hydrocarbon purification catalyst composition, a catalyst, a preparation method and application thereof. Background Art
[0002] During the process of coal coking, non-methane hydrocarbons will be emitted due to leakage, incomplete combustion or furnace wall leakage, which seriously pollutes the environment. On the one hand, it is the main precursor of atmospheric fine particulate matter (PM2.5), which is the main cause of urban haze pollution; on the other hand, under sunlight, non-methane hydrocarbons easily react with nitrogen oxides, leading to ozone pollution or photochemical smog, endangering the ecological environment and human health.
[0003] In the process of realizing the present invention, the applicant discovered that the traditional non-methane total hydrocarbon purification catalyst has a short life and a high cost due to sulfur intolerance. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of this, the present invention aims to at least partially solve one of the technical problems.
[0006] (II) Technical solution
[0007] In order to achieve the above purpose, according to the first aspect of the present invention, a non-methane total hydrocarbon purification catalyst composition is provided. The non-methane total hydrocarbon purification catalyst composition comprises:
[0008] The first component: soluble ferrous sulfate, or a mixture of soluble ferrous sulfate and soluble manganese sulfate;
[0009] The second component: alkaline earth metal hydroxide; wherein the alkaline earth metal hydroxide is Ba(OH)2 and / or Sr(OH)2;
[0010] The third component: manganese source compound;
[0011] The molar ratio of the first component to the second component is in the range of 1:0.6 to 1:1; the molar ratio of the first component to the third component is in the range of 1:0.27 to 1:0.40.
[0012] In some embodiments of the present invention, the manganese source compound is KMnO4, K2MnO4, NaMnO4 and / or Na2MnO4;
[0013] In some embodiments of the present invention, the soluble ferrous sulfate is FeSO4·7H2O, FeSO4·6H2O and / or FeSO4·5H2O.
[0014] In some embodiments of the present invention, the soluble manganese sulfate is MnSO4·4H2O and / or MnSO4·H2O; wherein, in the mixture of soluble ferrous sulfate and soluble manganese sulfate, the molar percentage of soluble manganese sulfate is between 5% and 50%.
[0015] In some embodiments of the present invention, the first component is FeSO4·7H2O; the second component is Ba(OH)2; wherein the molar ratio of FeSO4·7H2O, Ba(OH)2, and KMnO4 is 1:(0.4-1.2):(0.1-0.6).
[0016] In some embodiments of the present invention, the present invention further comprises: a fourth component: titanium sol or silica sol.
[0017] In order to achieve the above purpose, according to the second aspect of the present invention, a method for preparing a non-methane total hydrocarbon purification catalyst is also provided. The method for preparing a non-methane total hydrocarbon purification catalyst comprises the following steps:
[0018] Step A, solid-solid mixing and grinding the first component and the second component; wherein the first component is soluble ferrous sulfate, or a mixture of soluble ferrous sulfate and soluble manganese sulfate; wherein the second component is an alkaline earth metal hydroxide, and the alkaline earth metal hydroxide is Ba(OH)2 and / or Sr(OH)2;
[0019] Step B, adding a third component to the material obtained in step A for solid-solid mixing and grinding; wherein the third component is a manganese source compound;
[0020] Step D, adding a binder and a pore-forming agent to the material obtained in step B, mixing, grinding, molding, and drying to obtain a semi-finished catalyst;
[0021] Step F, calcining the semi-finished catalyst to obtain a non-methane total hydrocarbon purification catalyst.
[0022] In some embodiments of the present invention, step D and step F also include: step E, immersing the semi-finished catalyst in titanium sol or silica sol; wherein, if immersed in titanium sol, the titanium sol attached to the semi-finished catalyst forms a TiO2 shell layer on the surface of the non-methane total hydrocarbon purification catalyst after calcination; if immersed in silica sol, the silica sol attached to the semi-finished catalyst forms a SiO2 shell layer on the surface of the non-methane total hydrocarbon purification catalyst after calcination.
[0023] In some embodiments of the present invention, step E comprises: immersing the semi-finished catalyst in titanium sol, wherein the mass concentration of TiO2 in the titanium sol is 0.02% to 2%.
[0024] In some embodiments of the present invention, in step A, the first component is FeSO4·7H2O, and the second component is Ba(OH)2; and the solid-solid mixing time is between 30 and 60 minutes.
[0025] In some embodiments of the present invention, in step B, the manganese source compound is KMnO4, and the solid-solid mixing time is between 20 and 60 minutes.
[0026] In some embodiments of the present invention, between step B and step D, the following further comprises: step C, washing and drying the material obtained in step B to obtain a washed material; wherein the drying comprises: drying at 100° C. to 120° C. for 1 to 10 hours, or naturally air-drying for 12 to 24 hours; the step of adding a binder and a pore-forming agent to the material obtained in step B in step D comprises: adding a binder and a pore-forming agent to the washed material obtained in step C.
[0027] In some embodiments of the present invention, in step D, the binder includes: an inorganic binder and an organic binder, wherein the inorganic binder is selected from one or more of the following materials: titanium sol, silica sol, aluminum sol, and its mass percentage of the total amount of material after the addition of the inorganic binder is between 10% and 30%; the organic binder is selected from one or more of the following materials: carboxymethyl cellulose, sesbania gum; its mass percentage of the total amount of material after the addition of the organic binder is between 0.01% and 0.4%.
[0028] In some embodiments of the present invention, in step D, the pore-forming agent is selected from one or more of the following materials: starch, flour; and the mass percentage of the pore-forming agent in the total amount of the material after the pore-forming agent is added is between 0.1% and 5%.
[0029] In some embodiments of the present invention, in step D, the mixing and grinding time is 20 to 60 minutes; and the drying is: drying at 120° C. for 2 to 24 hours.
[0030] In some embodiments of the present invention, in step F, the calcination is performed at 350° C. to 700° C. for 1 to 4 hours.
[0031] In order to achieve the above purpose, according to the third aspect of the present invention, a non-methane total hydrocarbon purification catalyst is provided. The non-methane total hydrocarbon purification catalyst is prepared by the above preparation method and is in a granular or honeycomb shape.
[0032] In order to achieve the above purpose, according to the fourth aspect of the present invention, there is also provided an application of the above non-methane total hydrocarbon purification catalyst composition in removing non-methane total hydrocarbons in coke oven flue gas or an application of the above non-methane total hydrocarbon purification catalyst in removing non-methane total hydrocarbons in coke oven flue gas.
[0033] (III) Beneficial effects
[0034] It can be seen from the above technical solution that the present invention has at least one of the following beneficial effects:
[0035] (1) The applicant has learned through experiments and scientific analysis that non-precious metal catalysts are easily deactivated by sulfur and water due to their own properties. The main reason for sulfur deactivation is that sulfur reacts with active components to cause the active components to be sulfated. The presence of water will further aggravate the sulfateation of the active components.
[0036] In the present invention, the alkaline earth metal hydroxide adopts Ba(OH)2 and / or Sr(OH)2. The sulfates corresponding to the two materials are both water-insoluble and will not be dissolved by coke oven flue gas. They serve as carriers to disperse the active component Fe and the Mn added later, and have water resistance and sulfur-repellent effects, thereby improving the tolerance of the catalyst.
[0037] (2) In the present invention, FeSO4.7H2O, FeSO4.6H2O and / or FeSO4.5H2O are used as the main component of the first component.
[0038] First, Fe is chosen as the main element of the catalyst, mainly because iron oxide is a non-toxic catalyst and its sulfur resistance is better than that of relatively cheap metal oxides such as Cu, Mn, and Co. In addition, iron compounds are cheap and can be added in large quantities. Even if some of them are deactivated by sulfur, it does not affect the overall catalytic effect.
[0039] Secondly, experiments have shown that soluble ferrous sulfate must contain more than 5 crystal waters, otherwise, the poor solubility will affect the performance of the prepared catalyst. In particular, the catalytic performance of the catalyst prepared using FeSO4·H2O as the soluble ferrous sulfate raw material is about 90% lower than that of the catalyst using FeSO4·7H2O; while the catalyst prepared using ferric sulfate as the raw material has no catalytic effect at all. In addition, due to the poor stability of ferrous sulfate containing less than 5 crystal waters, the performance of the prepared catalyst is also unstable.
[0040] Finally, soluble manganese sulfate can be used to partially replace the soluble ferrous sulfate in the first component to balance the catalytic activity and sulfur resistance.
[0041] (3) Potassium permanganate is used as the manganese source compound. On the one hand, manganese and iron form a synergistic effect, further improving the catalytic activity. On the other hand, amorphous oxyhydroxide iron with smaller grains can be obtained by rapid oxidation with potassium permanganate. By controlling the calcination temperature and calcination time, nano-iron oxide can be obtained. Smaller grain size has a larger specific surface area and more lattice defects, which can provide more active sites.
[0042] (4) In the preparation method, FeSO4·7H2O and Ba(OH)2 are firstly solid-solid mixed and ground; then KMnO4 is added for solid-solid mixed and ground, so that the first component can fully react with the second component as follows:
[0043] FeSO4·7H2O+Ba(OH)2→BaSO4+Fe(OH)2+7H2O…………①
[0044] The reactants of the above reaction are then reacted with the manganese source compound to undergo the following second step reaction:
[0045] KMnO4+3Fe(OH)2→MnO2+3FeOOH+KOH+H2O…………②
[0046] The remaining first component in the first step reaction and the manganese source compound are further reacted as follows:
[0047] 10KMnO4+30FeSO4·7H2O→10MnO2+30FeOOH+5K2SO4+25H2SO4+170H2O ③
[0048] Through the above arrangement, the controllability of the reaction process and the purity of the generated substances are guaranteed.
[0049] (5) A layer of TiO2 shell is covered on the catalyst surface. TiO2 has strong sulfur and water resistance, which makes it difficult for SO2 to adsorb on the catalyst surface, thereby preventing the sulfation of active components and protecting the active components. However, the TiO2 shell cannot be too thick, as it will hinder the diffusion of non-methane total hydrocarbons and oxygen to the active sites. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 The present invention is a flow chart of the method for preparing a catalyst for purifying non-methane total hydrocarbons. DETAILED DESCRIPTION
[0051] The applicant has learned through experiments and scientific analysis that non-precious metal catalysts are easily deactivated by sulfur and water due to their own properties. The main reason for sulfur deactivation is the reaction with active components, which causes the active components to be sulfated. The presence of water will further aggravate the sulfation of the active components.
[0052] Based on the above research results, the present invention selects Fe as the main element of the catalyst, adds an active component sacrificial agent, uses in-situ generated water-insoluble alkaline earth metal sulfate as a carrier, and covers the catalyst surface with a TiO2 shell, so as to achieve the purpose of reducing the adsorption of SO2 on the catalyst surface and improving the catalyst's tolerance to SO2.
[0053] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings.
[0054] According to a first aspect of the present invention, a non-methane total hydrocarbon purification catalyst composition is provided. The non-methane total hydrocarbon purification catalyst composition comprises:
[0055] The first component: soluble ferrous sulfate, or a mixture of soluble ferrous sulfate and soluble manganese sulfate;
[0056] The second component: an alkaline earth metal hydroxide, wherein the alkaline earth metal hydroxide is Ba(OH)2 and / or Sr(OH)2;
[0057] The third component: manganese source compound;
[0058] The molar ratio of the first component to the second component is in the range of 1:0.6 to 1:1; the molar ratio of the first component to the third component is in the range of 1:0.27 to 1:0.40.
[0059] For the first component in the composition, the soluble ferrous sulfate is FeSO4·7H2O, FeSO4·6H2O and / or FeSO4·5H2O, and the soluble manganese sulfate is MnSO4·H2O and / or MnSO4·4H2O. Furthermore, if the first component is a mixture of soluble ferrous sulfate and soluble manganese sulfate, the molar percentage of the soluble manganese sulfate in the entire mixture is between 5% and 50%.
[0060] First, Fe is chosen as the main element of the catalyst, mainly because iron oxide is a non-toxic catalyst, and its sulfur resistance is better than that of relatively cheap metal oxides such as Cu, Mn, and Co. In addition, iron compounds are extremely cheap and can be added in large quantities. Even if some of them are deactivated by sulfur, it does not affect the overall catalytic effect.
[0061] Secondly, experiments have shown that soluble ferrous sulfate must contain more than 5 crystal waters, otherwise, the poor solubility will affect the performance of the prepared catalyst. In particular, experiments have shown that the catalytic performance of the catalyst prepared using FeSO4·H2O as the soluble ferrous sulfate raw material is 90% lower than that of the catalyst prepared using FeSO4·7H2O; while the catalyst prepared using ferric sulfate as the raw material has no catalytic effect at all. In addition, due to the poor stability of ferrous sulfate containing less than 5 crystal waters, the performance of the prepared catalyst is also unstable.
[0062] Finally, soluble manganese sulfate can be used to partially replace the soluble ferrous sulfate in the first component to balance the catalytic activity and sulfur resistance.
[0063] In the present invention, the manganese source compound is KMnO4, K2MnO4, NaMnO4 and / or Na2MnO4.
[0064] The manganese source compound in the composition is specifically KMnO4. On the one hand, manganese and iron form a synergistic effect to further improve the catalytic activity. On the other hand, through rapid oxidation with potassium permanganate, amorphous oxyhydroxide iron with smaller grains can be obtained, and nano iron oxide can be obtained by controlling the calcination temperature and calcination time. Smaller grain size has a larger specific surface area and more lattice defects, which can provide more active sites.
[0065] In a preferred embodiment of the present invention, the composition further includes titanium sol, which forms a TiO2 shell on the catalyst surface; or silica sol, which forms a SiO2 shell on the catalyst surface. Taking the TiO2 shell as an example, a layer of TiO2 shell is covered on the catalyst surface. TiO2 has strong sulfur and water resistance, which makes it difficult for SO2 to adsorb on the catalyst surface, thereby preventing the sulfation of the active components and protecting the active components. However, the TiO2 shell cannot be too thick, otherwise it will hinder the diffusion of non-methane total hydrocarbons and oxygen to the active sites. The principle and function of silica sol are similar to this and will not be repeated.
[0066] In a preferred embodiment of the present invention, the first component is FeSO4·7H2O; the second component is Ba(OH)2; the third component is KMnO4; and the fourth component is titanium sol. The molar ratio of FeSO4·7H2O, Ba(OH)2, and KMnO4 is 1:(0.4-1.2):(0.1-0.6). That is, based on the molar number of FeSO4·7H2O as 1 part, Ba(OH)2 is 0.4-1.2 parts, and KMnO4 is 0.1-0.6 parts. The composition with such a ratio has the best performance.
[0067] According to the second aspect of the present invention, a method for preparing a non-methane total hydrocarbon purification catalyst using the above non-methane total hydrocarbon purification catalyst composition is also provided. For the specific content of the non-methane total hydrocarbon purification catalyst composition, please refer to the relevant description above, which will not be repeated here.
[0068] Figure 1 FIG. 1 is a flow chart of the method for preparing a catalyst for purifying non-methane hydrocarbons in the present invention. Figure 1 As shown, the preparation method of the non-methane total hydrocarbon purification catalyst in the present invention comprises the following steps:
[0069] Step A, solid-solid mixing and grinding the first component and the second component;
[0070] Wherein, the first component is soluble ferrous sulfate, or a mixture of soluble ferrous sulfate and soluble manganese sulfate; wherein, the second component is alkaline earth metal hydroxide, and the alkaline earth metal hydroxide is Ba(OH)2 and / or Sr(OH)2.
[0071] The ratio of FeSO4·7H2O to alkaline earth metal hydroxide is 1:0.6 to 1:1, preferably 1:0.8 to 1:0.85. The main purpose is to allow all the alkaline earth metal hydroxide to react to avoid residue (such as formula ①). The excess FeSO4·7H2O can neutralize the alkalinity of KMnO4 after the reaction.
[0072] FeSO4·7H2O+Ba(OH)2→BaSO4+Fe(OH)2+7H2O…………①
[0073] The alkaline earth hydroxide is barium hydroxide and / or strontium hydroxide. Other alkaline earth metal or alkali metal sulfates are water-soluble to a certain extent, and the coke oven flue gas contains a high content of water, so other alkaline earth metal or alkali metal hydroxides are not suitable. The generated alkaline earth metal sulfate, such as BaSO4, acts as a carrier to disperse the active component Fe and the Mn added later, and also improves the sulfur resistance of the catalyst.
[0074] The solid-solid mixing and grinding process uses a mixing and grinding machine or a kneading machine for 20 to 60 minutes, preferably 20 to 40 minutes. Solid-solid reaction is slower than solution reaction. Prolonging the mixing and grinding time is conducive to sufficient reaction. However, too long mixing and grinding time will increase the Fe 2+ It will slowly oxidize in the air. The product obtained by slow oxidation has larger grains, which is not conducive to catalysis. Therefore, the solid-solid mixing time cannot be too long.
[0075] Step B, adding a third component to the material obtained in step A for solid-solid mixing and grinding;
[0076] Preferably, the third component is a manganese source compound.
[0077] Specifically, for step B, KMnO4 is used as a manganese source to form a synergistic effect with Fe to improve the catalytic performance. In addition, it acts as a strong oxidant to quickly oxidize Fe. 2+ The product has smaller crystals and better activity. The molar ratio of FeSO4·7H2O to KMnO4 is 1:0.27 to 1:0.40, preferably 1:0.30 to 1:0.37.
[0078] This reaction can be broken down into two reactions: KMnO4 oxidizing Fe(OH)2 (equation ②), and KMnO4 oxidizing the excess FeSO4·7H2O in the system (equation ③). If there is no acid to neutralize the generated KOH in reaction ②, the reaction will not be complete and the product will contain potassium manganate. Therefore, the excess FeSO4·7H2O in step A is to neutralize the generated KOH.
[0079] KMnO4+3Fe(OH)2→MnO2+3FeOOH+KOH+H2O………………②
[0080] 10KMnO4+30FeSO4·7H2O→10MnO2+30FeOOH+5K2SO4+25H2SO4+170H2③
[0081] Formula ②×50+Formula ③, we get Formula ④:
[0082] 60KMnO4+150Fe(OH)2+30FeSO4·7H2O→60MnO2+180FeOOH+30K2SO4+270H2O....④
[0083] Formula ④ is reduced to the common divisor 30, and we get formula ⑤
[0084] 2KMnO4+5Fe(OH)2+FeSO4·7H2O→2MnO2+6FeOOH+K2SO4+9H2O…⑤
[0085] Therefore, taking Ba(OH)2 as the alkaline earth metal hydroxide as an example, the molar ratio of each reactant is:
[0086] FeSO4·7H2O / Ba(OH)2 / KMnO4=6 / 5 / 2
[0087] Therefore, if the molar amount of FeSO4·7H2O is 1, the optimal molar amount of Ba(OH)2 is 0.83, and the optimal molar amount of KMnO4 is 0.33.
[0088] Step C, washing and drying the material obtained in step B to obtain a washed material;
[0089] For step C, the main purpose of this step is to wash away the generated K2SO4 with water. It is also possible not to wash with water, but K2SO4 will absorb water in the atmosphere during use, covering some active sites, which will affect the activity of the catalyst to a certain extent. In addition, drying is to remove some moisture, otherwise the material is too wet to be extruded.
[0090] Step D, adding a binder and a pore-forming agent to the washed material, mixing, grinding, molding, and drying to obtain a semi-finished catalyst;
[0091] For step D, the inorganic binder forms a metal oxide skeleton after calcination, which mainly provides the strength of the final catalyst. The inorganic binder refers to one or two or more of titanium sol, silica sol, and aluminum sol, respectively calculated as TiO2, SiO2, and Al2O3, and the added amount is converted to a mass content of 10% to 30%. For example: A is the mass of the material, and B is the mass of the glue calculated as TiO2, SiO2, and Al2O3, then B / (A+B)*100% should be equal to 10% to 30%, preferably 15% to 25%.
[0092] Organic binders are added in very small amounts, have good viscosity, and have good lubrication effects. They are mainly used to facilitate extrusion molding and provide semi-finished product strength. They are completely or partially lost after roasting and have a certain pore-forming effect. Organic binders refer to a mixture of one or two of carboxymethyl cellulose and sesbania gum. The amount added is converted to a mass content of 0.01% to 0.4% on a dry basis. For example: A is the mass of the material, and B is the mass of the gum calculated on a dry basis, then B / (A+B)*100% should be equal to 0.01% to 0.4%, preferably 0.05% to 0.2%.
[0093] The pore-forming agent is converted into CO2 and H2O after calcination and then lost to form cavities. Its main function is to increase the pore volume and specific surface area of the final catalyst. However, if the amount is too much, the strength will decrease. The pore-forming agent refers to a mixture of starch or flour or both. The amount added is converted to a mass content of 0.1% to 5%, preferably 0.5% to 1.5%.
[0094] After extrusion molding, it needs to be dried to remove free water. The drying time is determined by the drying efficiency. Extrusion molding can be honeycomb, strip, etc., and there is no need to make too many restrictions here.
[0095] Step E, immersing the semi-finished catalyst in titanium sol;
[0096] The titanium sol attached to the semi-finished catalyst forms a TiO2 shell layer after being dried and calcined, and the mass concentration of TiO2 in the titanium sol is 0.02% to 2%.
[0097] In addition, the titanium sol as above can also be replaced by silica sol. In this case, the silica sol is dried and calcined to form a SiO2 shell layer.
[0098] For step E, the dried semi-finished catalyst is impregnated with titanium sol. The purpose is to cover the catalyst surface with a TiO2 shell after calcination. TiO2 has strong sulfur and water resistance, which makes it difficult for SO2 to adsorb on the catalyst surface, thereby preventing the sulfation of the active components and protecting the active components. However, the TiO2 shell cannot be too thick, otherwise it will hinder the diffusion of non-methane total hydrocarbons and oxygen to the active sites. It is difficult to measure the shell thickness, which is limited by the TiO2 concentration in the impregnation solution. The mass concentration of TiO2 in the impregnation solution is 0.02% to 2%, preferably 0.05% to 1%. It needs to be dried again after impregnation.
[0099] Step F, calcining the semi-finished catalyst to obtain a finished non-methane total hydrocarbon purification catalyst.
[0100] In a preferred embodiment of the present invention, the preparation method of the above non-methane total hydrocarbon purification catalyst specifically comprises:
[0101] Step A, solid-solid mixing of FeSO4·7H2O and alkaline earth metal hydroxide for 30 to 60 minutes;
[0102] Step B, adding KMnO4 to the mixed and milled material and then mixing and milling for 20 to 60 minutes;
[0103] Step C, washing the mixed and ground material with water to remove the soluble salt K2SO4, drying at 100-120°C for 1-10 hours, or air-drying for 12-24 hours;
[0104] Step D, adding an inorganic binder, an organic binder and a pore-forming agent to the washed material, mixing and grinding for 20 to 60 minutes; then extruding and molding, and drying at 120° C. for 2 to 24 hours;
[0105] Step E, impregnating the shaped and dried catalyst with titanium sol to attach a layer of titanium sol to the surface, and then drying at 120° C. for 2 to 10 hours;
[0106] Step F, calcining at 350-700°C for 1-4 hours to obtain the finished catalyst.
[0107] Among them, the calcination temperature is preferably 350 to 550°C.
[0108] According to a third aspect of the present invention, a non-methane total hydrocarbon purification catalyst is provided. The non-methane total hydrocarbon purification catalyst is prepared by the preparation method described above and is in a granular or honeycomb shape.
[0109] According to a fourth aspect of the present invention, there is also provided a use of the above-mentioned non-methane total hydrocarbon purification catalyst composition or the above-mentioned non-methane total hydrocarbon purification catalyst in removing non-methane total hydrocarbons from coke oven flue gas.
[0110] The present invention is described in detail below with reference to specific embodiments.
[0111] Comparative Example 1
[0112] Step A', solid-solid mixing of FeSO4·7H2O and Ca(OH)2 for 20 min;
[0113] Step B', adding KMnO4 to the obtained material and then solid-solid mixing and grinding for 15 minutes; wherein the molar ratio of each reactant is: FeSO4·7H2O / Ca(OH)2 / KMnO4=2 / 5 / 6;
[0114] Step C', adding the obtained material to an inorganic binder, an organic binder and a pore-forming agent, and mixing and grinding for 15 minutes; then extruding and molding, and drying at 120° C. for 2 hours;
[0115] The test shows that the 10% conversion temperature (T10) of propane is 280°C, and the 90% conversion temperature (T90) is 400°C; at the T90 temperature, 10% water vapor and 10 ppm SO2 are introduced, and the deactivation rate is 0.863% / h.
[0116] Example 1
[0117] Step A, solid-solid mixing of FeSO4·7H2O and Ba(OH)2 for 30 minutes;
[0118] Step B, adding KMnO4 to the obtained material and then solid-solid mixing and grinding for 20 minutes; wherein the molar ratio of each reactant is: FeSO4·7H2O / Ba(OH)2 / KMnO4=6 / 5 / 2;
[0119] Step C, washing the obtained material with water to remove the soluble salt K2SO4, and drying at 100°C for 1 hour;
[0120] Step D, adding inorganic binder: and organic binder: and pore-forming agent: to the washed material, and mixing and grinding for 20 minutes; then extruding and molding, and drying at 120° C. for 2 hours;
[0121] Step E, impregnating the shaped and dried catalyst with titanium sol to attach a layer of titanium sol to the surface, and then drying at 120° C. for 2 hours; wherein the mass concentration of TiO2 in the impregnation solution is 0.02%;
[0122] Step F, calcining at 350°C for 4 hours to obtain the finished catalyst.
[0123] According to the test, the 10% conversion temperature (T10) of propane is 150°C, and the 90% conversion temperature (T90) is 230°C; at the T90 temperature, 10% water vapor and 10 ppm SO2 are introduced, and the deactivation rate is 0.005% / h.
[0124] Example 2
[0125] This embodiment is similar to Embodiment 1, except that 50 mol% FeSO4·7H2O and 50 mol% MnSO4·1H2O are used to replace FeSO4·7H2O in step A.
[0126] The test shows that the 10% conversion temperature (T10) of propane is 125°C, and the 90% conversion temperature (T90) is 210°C; at the T90 temperature, 10% water vapor and 10 ppm SO2 are introduced, and the deactivation rate is 0.020% / h.
[0127] Example 3
[0128] This embodiment is similar to embodiment 1, except that FeSO4·5H2O is used instead of FeSO4·7H2O in step A. Tests show that the 10% conversion temperature (T10) of propane is 185°C, and the 90% conversion temperature (T90) is 270°C; at T90, 10% water vapor and 10 ppm SO2 are introduced, and the deactivation rate is 0.009% / h.
[0129] Example 4
[0130] This embodiment is similar to Embodiment 1, except that 75% by mole of FeSO4.7H2O and 25% by mole of MnSO4.1H2O are used to replace FeSO4.7H2O in Step A.
[0131] The test shows that the 10% conversion temperature (T10) of propane is 130°C, and the 90% conversion temperature (T90) is 225°C; at the T90 temperature, 10% water vapor and 10 ppm SO2 are introduced, and the deactivation rate is 0.012% / h.
[0132] Example 5
[0133] This embodiment is similar to embodiment 1, except that Sr(OH)2 is used instead of Ba(OH)2 in step A.
[0134] The test shows that the 10% conversion temperature (T10) of propane is 155°C, and the 90% conversion temperature (T90) is 240°C; at the T90 temperature, 10% water vapor and 10 ppm SO2 are introduced, and the deactivation rate is 0.007% / h.
[0135] Example 6
[0136] This embodiment is similar to embodiment 1, except that Na2MnO4 is used instead of KMnO4 in step B.
[0137] The test shows that the 10% conversion temperature (T10) of propane is 170°C, and the 90% conversion temperature (T90) is 265°C; at the T90 temperature, 10% water vapor and 10 ppm SO2 are introduced, and the deactivation rate is 0.016% / h.
[0138] Example 7
[0139] This embodiment is similar to embodiment 1, except that the molar ratio of the reactants is: FeSO4·7H2O / Ba(OH)2 / KMnO4=6 / 4 / 3.
[0140] According to the test, the 10% conversion temperature (T10) of propane is 170°C, and the 90% conversion temperature (T90) is 280°C; at the T90 temperature, 10% water vapor and 10 ppm SO2 are introduced, and the deactivation rate is 0.015% / h.
[0141] Example 8
[0142] This embodiment is similar to Embodiment 1, except that step C' is omitted.
[0143] The test shows that the 10% conversion temperature (T10) of propane is 200°C, and the 90% conversion temperature (T90) is 300°C; at the T90 temperature, 10% water vapor and 10 ppm SO2 are introduced, and the deactivation rate is 0.054% / h.
[0144] Example 9
[0145] This embodiment is similar to the embodiment 1, except that the titanium sol in step E' is replaced with silica sol, wherein the mass concentration of SiO2 in the silica sol is 2%.
[0146] The test shows that the 10% conversion temperature (T10) of propane is 240°C, and the 90% conversion temperature (T90) is 330°C; at the T90 temperature, 10% water vapor and 10 ppm SO2 are introduced, and the deactivation rate is 0.007% / h.
[0147] Example 10
[0148] This embodiment is similar to Embodiment 1, except that:
[0149] In step A, the solid-solid mixing time is 60 minutes;
[0150] In step B, the solid-solid mixing time is 60 minutes;
[0151] In step C, natural air drying is used for 24 hours;
[0152] In step D, the mixing time is 60 minutes and the drying time is 24 hours;
[0153] In step E, the drying time is 10 hr;
[0154] In step F, calcination is carried out at 700°C for 1 hr.
[0155] The test shows that the 10% conversion temperature (T10) of propane is 270°C, and the 90% conversion temperature (T90) is 385°C; at the T90 temperature, 10% water vapor and 10 ppm SO2 are introduced, and the deactivation rate is 0.006% / h.
[0156] The 10% conversion temperature (T10), 90% conversion temperature (T90) and deactivation rate test method of propane described in the above embodiments of the present invention and comparative examples are:
[0157] 5g of catalyst was loaded into a fixed bed reactor. At normal pressure, a gas containing 200ppm of propane, 8% oxygen and the rest of nitrogen was introduced into the reactor inlet. The temperature was slowly raised. The outlet propane concentration and bed temperature were recorded. The conversion rate was calculated by the propane concentration, and the data of 10% conversion rate temperature (T10) and 90% conversion rate temperature (T90) of propane were obtained. The bed was kept at a constant temperature of T90, 10% of water vapor and 10ppm of SO2 were introduced, and the outlet propane concentration was recorded in real time. The conversion rate was calculated by the propane concentration, and the propane conversion rate and time curve was plotted. The deactivation rate was obtained by first-order fitting of the curve. The conversion rate calculation formula is as follows:
[0158]
[0159] So far, multiple embodiments of the present invention have been described in detail with reference to the accompanying drawings. Based on the above description, those skilled in the art should have a clear understanding of the present invention.
[0160] In addition, the above definitions of the various elements and methods are not limited to the various specific structures, shapes or methods mentioned in the embodiments, and those skilled in the art may make simple changes or substitutions therefor, for example:
[0161] (1) The water washing step in step C can be omitted; or the product can be washed with water after calcination and then dried at 120°C for 2 to 24 hours.
[0162] (2) The titanium sol in step E can also be replaced by silica sol, and the concentration range remains unchanged.
[0163] In summary, the present invention provides a non-methane total hydrocarbon purification catalyst composition, a catalyst, a preparation method and an application thereof. By selecting Ba(OH)2 and / or Sr(OH)2 as reactants, the corresponding active component carrier generated will not become ineffective due to dissolution in water, and has water resistance and sulfur-repelling effects, thereby improving the anti-sulfur performance of the catalyst. At the same time, by using FeSO4·7H2O as a reactant, more and more stable active components can be produced; by using potassium permanganate as a reactant, on the one hand, manganese can synergistically enhance the catalytic activity with iron, and on the other hand, "amorphous" hydroxyl iron with smaller grains can be obtained, and the calcination temperature and calcination time can be controlled to obtain nano iron oxide. Finally, the anti-sulfur and anti-water performance of the catalyst is improved by a TiO2 or SiO2 shell. By the above-mentioned various means, a non-methane total hydrocarbon purification catalyst with excellent anti-water and anti-sulfur performance is obtained, which has a good prospect for promotion and application.
[0164] It should be noted that, for certain implementations, if they are not the key content of the present invention and are well known to ordinary technicians in the relevant technical field, they are not described in detail in the drawings or the main text of the specification. In this case, they can be understood by referring to the relevant prior art.
[0165] Further, the purpose of providing the above embodiments is only to enable the present invention to meet legal requirements, and the present invention can be implemented in many different forms and should not be construed as being limited to the embodiments described herein. In addition, the above definitions of various elements and methods are not limited to the various specific structures, shapes or methods mentioned in the embodiments, and those of ordinary skill in the art can simply modify or replace them.
[0166] Unless expressly indicated to the contrary, the numerical parameters in the specification and claims of the present invention may be approximate values and can be changed according to the content of the present invention. Specifically, all numbers used in the specification and claims to express the content of the composition, reaction conditions, etc. should be understood to be modified by the term "about" in all cases, and the meaning expressed is to include a change of ±10% in some embodiments, ±5% in some embodiments, ±1% in some embodiments, and ±0.5% in some embodiments by a specific number. Furthermore, the word "comprising" does not exclude the existence of steps not listed in the claims. The ordinal numbers used in the specification and claims, such as Arabic numerals, letters, etc., to modify the corresponding steps, do not mean that the step has any ordinal number, nor do they represent the order of one step and another step.
[0167] In addition, unless the steps are specifically described or must occur in sequence, the order of the above steps is not limited to the above list, and can be changed or rearranged according to the required design. And the above embodiments can be mixed and matched with each other or with other embodiments based on design and reliability considerations, that is, the technical features in different embodiments can be freely combined to form more embodiments.
[0168] The specific embodiments described above have detailed descriptions of the objectives, technical solutions and beneficial effects of the present invention. It should be understood that the above descriptions are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A non-methane total hydrocarbon purification catalyst composition, characterized in that: include: The first component: soluble ferrous sulfate, or a mixture of soluble ferrous sulfate and soluble manganese sulfate; The soluble ferrous sulfate is FeSO4·7H2O, FeSO4·6H2O and / or FeSO4·5H2O; The second component: alkaline earth metal hydroxide; wherein the alkaline earth metal hydroxide is Ba(OH)2 and / or Sr(OH)2; The third component: manganese source compound; The manganese source compound is KMnO4, K2MnO4, NaMnO4 and / or Na2MnO4; The fourth component: titanium sol or silica sol; Among them, the molar ratio of the first component to the second component is in the range of 1:0.6~1:1; the molar ratio of the first component to the third component is in the range of 1:0.27~1:0.
40.
2. The non-methane total hydrocarbon purification catalyst composition according to claim 1, characterized in that: The soluble manganese sulfate is MnSO4·4H2O and / or MnSO4·H2O; wherein, in the mixture of the soluble ferrous sulfate and the soluble manganese sulfate, the molar percentage of the soluble manganese sulfate is between 5% and 50%.
3. The non-methane total hydrocarbon purification catalyst composition according to claim 2, characterized in that: The first component is FeSO4·7H2O; The second component is Ba(OH)2.
4. A method for preparing a non-methane total hydrocarbon purification catalyst, characterized in that: The method of using the non-methane total hydrocarbon purification catalyst composition according to claim 1 comprises the following steps: Step A, solid-solid mixing and grinding the first component and the second component; Wherein, the first component is soluble ferrous sulfate, or a mixture of soluble ferrous sulfate and soluble manganese sulfate; Wherein, the second component is an alkaline earth metal hydroxide, and the alkaline earth metal hydroxide is Ba(OH)2 and / or Sr(OH)2; Step B, adding a third component to the material obtained in step A for solid-solid mixing and grinding; Wherein, the third component is a manganese source compound; Step D, adding a binder and a pore-forming agent to the material obtained in step B, mixing, grinding, molding, and drying to obtain a semi-finished catalyst; Step E, immersing the semi-finished catalyst in titanium sol or silica sol; Step F, calcining the semi-finished catalyst to obtain the non-methane total hydrocarbon purification catalyst.
5. The preparation method according to claim 4, characterized in that: If immersed in titanium sol, the titanium sol attached to the semi-finished catalyst forms a TiO2 shell layer on the surface of the non-methane total hydrocarbon purification catalyst after calcination; If immersed in silica sol, the silica sol attached to the semi-finished catalyst forms a SiO2 shell layer on the surface of the non-methane total hydrocarbon purification catalyst after calcination.
6. The preparation method according to claim 5, characterized in that: The step E comprises: The semi-finished catalyst is immersed in titanium sol, and the mass concentration of TiO2 in the titanium sol is 0.02%~2%.
7. The preparation method according to claim 6, characterized in that: In step A, the first component is FeSO4·7H2O, and the second component is Ba(OH)2; the solid-solid mixing time is between 30 and 60 minutes; and / or In the step B, the manganese source compound is KMnO4, and the solid-solid mixing time is between 20 and 60 min; and / or The method further comprises the following steps between step B and step D: step C, washing and drying the material obtained in step B to obtain a washed material; wherein the drying comprises drying at 100° C. to 120° C. for 1 to 10 hours, or air drying for 12 to 24 hours; the step of adding a binder and a pore-forming agent to the material obtained in step B in step D comprises: adding a binder and a pore-forming agent to the washed material obtained in step C; and / or In the step D, the binder comprises: an inorganic binder and an organic binder, wherein the inorganic binder is selected from one or more of the following materials: titanium sol, silica sol, aluminum sol, and the mass percentage of the inorganic binder to the total amount of the material after the inorganic binder is added is between 10% and 30%; the organic binder is selected from one or more of the following materials: carboxymethyl cellulose, sesbania gum; the mass percentage of the organic binder to the total amount of the material after the organic binder is added is between 0.01% and 0.4%; and / or In step D, the pore-forming agent is selected from one or more of the following materials: starch, flour; the mass percentage of the pore-forming agent in the total amount of the material after the pore-forming agent is added is between 0.1% and 5%; and / or In the step D, the mixing and grinding time is 20 to 60 min; the drying is: drying at 120° C. for 2 to 24 hr; and / or In the step F, the calcination is performed at 350° C. to 700° C. for 1 to 4 hrs.
8. A catalyst for purifying non-methane total hydrocarbons, characterized in that: The catalyst is prepared by the preparation method described in any one of claims 4 to 7, and the non-methane total hydrocarbon purification catalyst is in a granular or honeycomb shape.
9. Use of the non-methane total hydrocarbon purification catalyst composition according to any one of claims 1 to 3 or the non-methane total hydrocarbon purification catalyst according to claim 8 in removing non-methane total hydrocarbons from coke oven flue gas.
Citation Information
Patent Citations
Preparation method of catalyst for catalytic combustion
CN103769085A
Ferrous sulfate-containing denitration catalyst and preparation method therefor
CN105363468A